The Labor Market in Azerbaijan - Ramiz Rahmanov; Asif Qasimov; Gulzar Tahirova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes the development of the labor market in Azerbaijan from the early 1990s until the early 2010s. The analysis shows that the labor market has a range of positive characteristics such as high labor force participation and employment, low youth and female unemployment, flexibility, and a low share of the "working poor", all of which can beneficially influence future economic prospects. However, the Azerbaijani labor market also experiences certain undesirable developments, such as an increase in the share of labor with primary education, a shift towards elementary occupations, a high share of self-employment, and an excess of labor cost growth over productivity growth, all of which can threaten further economic development.
Keywords: J21; J63; J65; P23; P31; 330; labor market; labor market flexibility; employment; unemployment; labor force; Azerbaijan